Tantangan Pendidikan Agama Islam di Madrasah Pada Era Globalisasi - Amirul Bakhri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
Madrasa as an educational institution established around the middle of the 5th century AD. The role of Islamic education in general and especially madrasa in the era of globalization must inevitably have to accept the times and technological advancements which are mostly sourced from western countries. So it should be, Islamic education madrasas must strive to develop themselves. So that it can make the students, not only successful with their IMTAQ, but also successful in facing the global world with its science and technology. This paper discusses the challenges of Islamic religious education in madrasas in the era of globalization. Some things that can be done by madrassas in an effort to increase the passion of Islamic education in the era of globalization are as follows: Improving the quality of Islamic religious education, Improving the curriculum of religious education, Identifying and analyzing instructional problems and constraints faced by teachers in schools and parents at home in an effort to foster student moral development, along with alternative formulations for solving it.